Handbook on Promoting Social Justice in Education 2020
DOI: 10.1007/978-3-030-14625-2_128
|View full text |Cite
|
Sign up to set email alerts
|

Identity Safety and Its Importance for Academic Success

Abstract: While there are many external factors that contribute to the equity students do or do not experience, equally important are the internal or psychological factors that impact student performance. This chapter examines the need for identity safety in the classroom, and how the culture of a classroom (the unspoken messages) can create or inhibit equity of the psychological environment. The intersecting influences of student achievement goal orientations and classroom goal emphasis have a direct and significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 196 publications
(284 reference statements)
0
5
0
Order By: Relevance
“…Research with White participants has often found a low sense of ERI among White youth (J. S. Phinney & Rosenthal, 1992;Rogers et al, 2021), in addition to less exploration for White youth as compared to ethnically minoritized adolescents (Camacho et al, 2018;Rogers et al, 2021). There is an increased interest in studying the protective factors of ERI for minoritized youth (Lowe, 2020), yet a lack of research investigating long-term educational implications of strong or weak ERI, especially pertaining to college enrollment.…”
Section: Adolescent Self-systemmentioning
confidence: 99%
“…Research with White participants has often found a low sense of ERI among White youth (J. S. Phinney & Rosenthal, 1992;Rogers et al, 2021), in addition to less exploration for White youth as compared to ethnically minoritized adolescents (Camacho et al, 2018;Rogers et al, 2021). There is an increased interest in studying the protective factors of ERI for minoritized youth (Lowe, 2020), yet a lack of research investigating long-term educational implications of strong or weak ERI, especially pertaining to college enrollment.…”
Section: Adolescent Self-systemmentioning
confidence: 99%
“…The person(s) responsible for assessing the risk associated with this hazard must have input from better versed and trained resources in the diversity, equity, inclusion, and respect space. These people have been trained to view an environment from an equity perspective, which may influence the ability of people to learn, feel included, or perform . Furthermore, applications of critical race theory in these scenarios have shown that higher concentrations of similar but diverse identities in a setting can often remove the perception of stereotypes, judgments, or restrictions for the individual, as they place a value on diversity and inclusion in that space.…”
Section: Assess the Riskmentioning
confidence: 99%
“…Exposure to identity threats can lead to several outcomes, including increased concerns about belonging, fit, and acceptance; ,, decreased trust; , increased anxiety; impaired executive functioning; disparities in job and career satisfaction and career aspirations; lower job performance and fewer promotions from supervisors; and increased turnover and absenteeism. ,− Diverse persons entering spaces that lack diversity start by asking questions about connecting with others, being valued, and being seen as more than the stereotypes of their identity. ,, Sustained exposure to these threats has been linked to increased self-reliance, acting as less of a team player, overworking beyond exhaustion, increased stress levels, and inability to sleep. In a laboratory setting, these symptoms would lead to depression, burnout, increased sick days, decreased productivity, inability to abide by laboratory protocols, increased hazardous activity, and physically unsafe behaviors with the materials they handle. Ultimately, these can lead to an increased turnover and, worse, injuries.…”
Section: Assess the Riskmentioning
confidence: 99%
“…That is, certain cues in community settings can either affirm or devalue youths' lived experiences and social identities (Davies et al, 2005 ; Steele & Cohn‐Vargas, 2013 ). A substantial body of research has found that identity‐safe contexts—settings that acknowledge differences in social identity and treat those differences as valuable—are an important component for development among underrepresented youth (Gamarel et al, 2014 ; Lowe, 2020 ; Purdie‐Vaughns et al, 2008 ). However, less is known about how diverse groups of youth and adults collaboratively develop identity safety in a community setting.…”
Section: Introductionmentioning
confidence: 99%
“…Identity-safe environments articulate how contexts can promote connection in the face of the isolation that arises from alienating sociocultural stereotypes. Much of the existing empirical research on identity-safety has been conducted within the context of schools, such as the impact of identity-safe cues for Latina students' interest in science, technology, engineering, and math (e.g., Goyer et al, 2019;Lowe, 2020;Pietri et al, 2019). Most of this study has documented the strategies that adults use to create identity safety or youth's experiences with identity safety in the classroom (e.g., Cooper, 2013;Steele & Cohn-Vargas, 2013), with less focus on intergenerational collaboration involved in this process.…”
Section: Introductionmentioning
confidence: 99%